Gastro-protective, therapeutic and anti-inflammatory activities of Pistacia lentiscus L. fatty oil against ethanol-induced gastric ulcers in rats. (5th October 2018) - Boutemine, Insaf-Meriem; Amri, Manel; Amir, Zine-Charaf; Fitting, Catherine; Mecherara-Idjeri, Samira; Layaida, Karim; Sennoun, Nacira; Berkane, Saadi; Cavaillon, Jean-Marc; Touil-Boukoffa, Chafia
Abstract: Ethnopharmacological relevance: Pistacia lentiscus L. (Anacardiaceae) (PL) is a flowering plant that grows in the Mediterranean area. It is traditionally used in the treatment of various skin, respiratory and gastrointestinal disorders Aim of the study: In the present study, we investigated the anti-ulcerogenic activity of Pistacia lentiscus fatty oil (PLFO) on ethanol-induced gastric ulcers in Wistar rats Material and methods: PLFO was orally administered to two experimental groups of rats before or after ethanol induction of gastric ulcer. The lesions of the gastric mucosa were evaluated by macroscopic and histopathological examination. In addition, the amount of nitric oxide (NO) and pro-inflammatory cytokines [tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)] in the supernatant from cultures of gastric mucosa explants were assessed. Finally, the mucus production and iNOS (inducible NO synthase) expression were determined by histochemical and immunohistochemical analysis, respectively Result: Our results indicated that the PLFO pretreatment or PLFO treatment significantly reduced ulcerated and hemorrhagic areas. Additionally, pretreatment or treatment with PLFO after ethanol-induced ulceration significantly reduced the plasma concentration of NO. Furthermore, a significant decrease of NO, IL-6 and TNF-α levels was observed in explant culture supernatants. iNOS expression was also reduced in the gastric mucosa. In contrast, mucus production by goblet cells was enhanced. Interestingly, histological analysis of the gastric mucosa has indicated that PLFO- pretreated and treated groups displayed normal histology Conclusion: Our results demonstrate that PLFO display significant prophylactic and therapeutic effects against gastric ulcers. Importantly, the mechanism underlying PLFO activities might implicate inhibition of inflammatory responses during gastric ulcer. Graphical abstract: fx1